Contemporary Neurobehavioral Syndromes. - Goldstein, Gerald (Taylor & Francis, 2011)
This volumes provides expert reviews of research involving new neurobehavioral syndromes defined as illnesses that first appeared, or were reconceptualized, during the twentieth century. These new disorders are reviewed with regard to their neurocognitive characteristics, causes, and outcomes to give researchers and clinicians an invaluable and up-to-date resource.